Development Of An Econometric Model Case Study: Romanian Classification System - Savescu Roxana (Studies in Business and Economics, 2015)
The purpose of the paper is to illustrate an econometric model used to predict the lean meat content in pig carcasses, based on the muscle thickness and back fat thickness measured by the means of an optical probe (OptiGrade PRO).The analysis goes through all steps involved in the development of the model: statement of theory, specification of the mathematical model, sampling and collection of data, estimation of the parameters of the chosen econometric model, tests of the hypothesis derived from the model and prediction equations. The data have been in a controlled experiment conducted by the Romanian Carcass Classification Commission in 2007. The purpose of the experiment was to develop the prediction formulae to be used in the implementation of SEUROP classification system, imposed by European Union legislation. The research methodology used by the author in this study consisted in reviewing the existing literature and normative acts, analyzing the primary data provided by and organization conducting the experiment and interviewing the representatives of the working team that participated in the trial.